Simultaneous Treatment of Photobiomodulation and Demineralized Bone Matrix With AdiposeDerived Stem Cells Improve Bone Healing in an osteoporotic bone defect: PBM, Plus DBM, and hASCs for Osteogenesis in Osteoporosis - Gazor, Rouhallah; Asgari, Mehrdad; Abdollajhifar, Mohammad Amin; Kiani, Pejman; Zare, Fatemeh; Fadaei Fathabady, Fatemeh; Norouzian, Mohsen; Amini, Abdollah; Khosravipour, Armin; Atashgah, Rahimeh B; et al. (Journal of Lasers in Medical Sciences, 2021)
Introduction: The ability of simultaneous treatment of critical-sized femoral defects (CSFDs) with photobiomodulation (PBM) and demineralized bone matrix (DBM) with or without seeded adipose-derived stem cells (ASCs) to induce bone reconstruction in ovariectomized induced osteoporotic (OVX) rats was investigated. Methods: The OVX rats with CSFD were arbitrarily separated into 6 groups: control, scaffold (S, DBM), S + PBM, S + alendronate (ALN), S + ASCs, and S + PBM + ASCs. Each group was assessed by cone-beam computed tomography (CBCT) and histological examinations. Results: In the fourth week, CBCT and histological analyses revealed that the largest volume of new bone formed in the S + PBM and S + PBM + ASC groups. The S + PBM treatment relative to the S and S + ALN treatments remarkably reduced the CSFD (Mann-Whitney test, P = 0.009 and P = 0.01). Furthermore, S + PBM + ASCs treatment compared to the S and S + ALN treatments significantly decreased CSFD (Mann Whitney test, P = 0.01). In the eighth week, CBCT analysis showed that extremely enhanced bone regeneration occurred in the CSFD of the S + PBM group. Moreover, the CSFD in the S + PBM group was substantially smaller than S, S + ALN, and S + ASCs groups (Mann Whitney test, P = 0.01, P = 0.02 and P = 0.009). Histological observations showed more new bone formation in the treated CSFD of S + PBM + ASCs and S + PBM groups. Conclusion: The PBM plus DBM with or without ASCs significantly enhanced bone healing in the CSFD in OVX rats compared to control, DBM alone, and ALN plus DBM groups. The PBM plus DBM with or without ASCs significantly decreased the CSFD area compared to either the solo DBM or ALN plus DBM treatments. DOI:10.34172/jlms.2021.41